Optimal scheduling of the RIES considering time-based demand response programs with energy price. (1st December 2018) - Wang, Yongli; Huang, Yujing; Wang, Yudong; Zeng, Ming; Yu, Haiyang; Li, Fang; Zhang, Fuli
Abstract: With the revolution of the traditional economic and social pattern based on centralized fossil energy consumption, the regional integrated energy system (RIES) has gained rapid development in recent years for achieving higher energy efficiency. This paper expands the Demand Response (DR) concept to the RIES and presents an optimal operation model of RIES considering the DR mechanism on the energy price. In this paper, a comprehensive DR strategy combining energy price and different loads is firstly developed to exploit the demand flexibility of RIES in the DR model established. Based on the DR modeling of the RIES, an operation optimization model with environmental, economic benefits and energy supply reliability as objective functions has been firstly established in detail. Secondly, a complete scheduling scheme is built based on the energy consumption characteristics and system operation characteristic of the integrated energy system. The model presented could reduce the cost of system without causing a significant amount of environmental pollution, and improve the energy efficiency of the RIES efficiently. Besides, the scheduling strategy proposed could also provide support for the operation strategy of integrated energy system under the energy development. Hopefully, this paper will provide reference for future research and engineering projects on DR programs in the RIES. Highlights: The typical structure of the RIES is introduced. A DR model suitable for the RIES considering different loads is established. An optimal operation model of the RIES based on DR is established. The load in the RIES is affected not only by energy price but also by other loads.